2022
DOI: 10.1089/ham.2021.0043
|View full text |Cite
|
Sign up to set email alerts
|

Stroke at Moderate and High Altitude

Abstract: Background: Stroke at high altitude is an understudied area in stroke research. With improvements in road infrastructure, access to high-altitude areas for recreation and living purposes has risen. Subsequently, it has been anticipated that due to normal physiological changes to high altitude the incidence of stroke is also likely to increase in these regions. Methods: We searched PubMed for available literature about stroke at high altitude. Cross-referencing was done from available articles and through other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…This is because people like to drink alcohol and eat high-fat foods, such as beef, mutton and animal offal, to keep warm to resist the cold climate and low-calorie, hypoxic environment. [42][43][44] Studies have found that smoking cessation can reduce stroke incidence and improve stroke prognosis and recurrence. A 2018 foreign study showed that quitting smoking within 6 months of a stroke or transient ischaemic attack significantly reduced the incidence of recurrent stroke, myocardial infarction or death within 4.8 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because people like to drink alcohol and eat high-fat foods, such as beef, mutton and animal offal, to keep warm to resist the cold climate and low-calorie, hypoxic environment. [42][43][44] Studies have found that smoking cessation can reduce stroke incidence and improve stroke prognosis and recurrence. A 2018 foreign study showed that quitting smoking within 6 months of a stroke or transient ischaemic attack significantly reduced the incidence of recurrent stroke, myocardial infarction or death within 4.8 years.…”
Section: Discussionmentioning
confidence: 99%
“…High-altitude residents are prone to hypertension, overweight or obesity and dyslipidaemia. This is because people like to drink alcohol and eat high-fat foods, such as beef, mutton and animal offal, to keep warm to resist the cold climate and low-calorie, hypoxic environment 42–44…”
Section: Discussionmentioning
confidence: 99%
“…(3) long-term stays (>60 days) above 2,500 m, to exclude highaltitude natives/residents and prolonged job-related sojourns (e.g., working in a hut or for the military); (4) intermittent bouts of hypoxic exposure; (5) studies including subjects exclusively in a sitting position during hypoxic exposure, to exclude venous stasis ("travel thrombosis") as a potential confounder; (6) patients with preexisting diseases possibly interfering with hemostasis; (7) studies on HAPE and high-altitude cerebral edema (HACE) patients [although studies with a clearly defined asymptomatic population (control group) were included for further analysis]; and 8) any form of medical treatment interfering with hemostasis.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…These "coagulopathies" at high altitude mostly present as venous thrombosis or/and venous thromboembolism (VTE; deep venous thrombosis, pulmonary thromboembolism, mesenteric vein thrombosis, and cerebral venous sinus thrombosis [CVST]) (3)(4)(5). Cases of coronary stent thrombosis have even been reported, and cerebrovascular stroke occurring at high altitude was discussed in association with increased thrombogenicity (6). In the literature, a multitude of articles point to high altitude itself as an independent factor for adverse changes in the hemostatic system (7).…”
Section: Introductionmentioning
confidence: 99%
“…Among different types of cerebrovascular disorders, cerebral infarction accounts for 48.4%, cerebral haemorrhage for 37.2%, subarachnoid haemorrhage for 9.8% and cerebral embolism for 4.6%. It has been observed that individuals residing in high-altitude areas have a higher prevalence of various cerebrovascular disorders, with ischaemic cerebrovascular diseases being the most common 3…”
Section: Introductionmentioning
confidence: 99%